Cobalt-based oxygen evolution catalyst and preparation method and application thereof
By coating the cobalt-based boride nanosheet layer on the carbon-based material to form a cobalt-based oxygen evolution catalyst with a petal structure, the problem of insufficient catalyst activity and stability in the prior art is solved, and the efficiency and stability of the electrolytic oxygen evolution reaction is significantly improved.
Patent Information
- Application Number
- CN202411724865.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the prior art, the activity and stability of transition metal-based catalysts are insufficient, which limits the development of electrolytic hydrogen production technology, especially in the oxygen evolution reaction, which is slower in reaction kinetics, which affects the efficiency of the catalyst.
By covering a uniform cobalt-based boride nanosheet layer on the carbon-based material, a cobalt-based oxygen evolution catalyst with a petal structure is formed, which improves the specific surface area and active sites of the catalyst and enhances its electrochemical oxygen evolution reaction activity in an alkaline environment.
The catalyst can reach a current density of 10mA/cm2 under electrolytic water conditions of 25°C and 1M KOH at a voltage of 1.479V, and performed well in a 20-hour stability test, with an overpotential less than or equal to 249mV, significantly improving the efficiency and stability of the oxygen evolution reaction.
Smart Images

Figure CN119592986A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a cobalt-based oxygen evolution catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen production technologies can be mainly divided into the following three categories: 1) hydrogen production from fossil fuels, 2) hydrogen production from biomass, and 3) hydrogen production from water electrolysis. Fossil fuel hydrogen production technologies are mature, such as industrial natural gas hydrogen production (SMR) and coal hydrogen production, but the hydrogen production process will emit a large amount of carbon dioxide, polluting the environment; biomass hydrogen production has a small carbon dioxide emission, but the instability of the hydrogen production process limits its large-scale hydrogen production application; in contrast, water electrolysis hydrogen production technology is environmentally friendly and pollution-free, and can be combined with wind power, solar energy and other power generation technologies for large-scale hydrogen production. It is a sustainable technology for producing green hydrogen fuel and has broad development prospects.
[0003] Hydrogen production by water electrolysis uses the electrolysis reaction of water to prepare "green hydrogen". The catalysts for water electrolysis are mainly divided into two categories: precious metals and non-precious metals. Precious metal catalysts have high catalytic activity, but their small earth reserves and high costs limit their large-scale industrial application. Non-precious metal catalysts mainly include transition metal-based compounds and carbon-based catalysts, which have the advantages of low cost but limited activity. Therefore, how to improve the activity and stability of transition metal-based catalysts has become a hot topic and difficulty in research. From the perspective of the reaction mechanism of water electrolysis, the hydrogen evolution reaction is a two-electron reaction process, while the oxygen evolution reaction involves a four-electron reaction process with slower reaction kinetics. Therefore, the development of efficient and durable oxygen evolution reaction catalysts is of great significance to the development of water electrolysis hydrogen production technology.
[0004] The prior art discloses a Co-B / Co-MOF nanomaterial and its preparation method and application (CN113463125B). The operation flow of preparing the material by this method is complicated and is not conducive to large-scale commercial use. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides a cobalt-based oxygen evolution catalyst and a preparation method and application thereof. The cobalt-based oxygen evolution catalyst obtained by the present invention is coated with a uniform cobalt-based boride nanosheet layer on a carbon-based material to form a petal structure. The catalyst has good catalytic performance for oxygen evolution reaction in electrolytic water.
[0006] The technical solution provided by the present invention is as follows:
[0007] A method for preparing a cobalt-based oxygen evolution catalyst comprises the following steps:
[0008] Step 1: Pretreatment: ultrasonically treat the carbon cloth electrode in ethanol, acetone, and deionized water in turn, and then wash and dry to obtain the carbon cloth electrode material;
[0009] Step 2: Hydrophilic treatment: Soak the carbon cloth in a mixture of concentrated sulfuric acid and concentrated nitric acid, then wash and dry with deionized water;
[0010] Step 3: dissolving a certain amount of cobalt salt in deionized water to form solution A; dissolving a certain amount of 2-methylimidazole in deionized water to form solution B;
[0011] Step 4: placing the carbon cloth obtained in step 2 into solution A for 5 minutes of ultrasonic treatment, then slowly adding solution B and stirring continuously for reaction; washing the carbon cloth after the reaction with deionized water and anhydrous ethanol alternately, and then placing it in a vacuum drying oven for drying to prepare a carbon cloth having a cobalt-based precursor material;
[0012] Step 5: Weigh a certain amount of cobalt salt, sodium succinate (C4H4Na2O4), sodium sulfate and dimethylaminoborane (C2H 10 BN), add deionized water to make a uniform solution C;
[0013] Step 6: Place the carbon cloth with the cobalt-based precursor material obtained in step 4 into the solution C prepared in step 5 to perform a mild boronization process, take it out after the reaction, wash it with deionized water, and then place it in a vacuum drying oven for drying;
[0014] Step 7: calcining the material obtained in step 6 to obtain a cobalt-based boride catalyst electrode material.
[0015] Specifically, in step 2:
[0016] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:(0.9-1.1);
[0017] The soaking time is 10 to 14 hours.
[0018] Specifically, in step 3:
[0019] The cobalt salt is cobalt nitrate hexahydrate, and the molar concentration of cobalt ions is 0.055-0.065 mol / L;
[0020] The molar concentration of 2-methylimidazole is 0.45-0.50 mol / L;
[0021] The reaction time is: stirring for 5.5 to 6.5 hours and settling for 5.5 to 6.5 hours.
[0022] Specifically, in step 4: the temperature of the vacuum drying oven is 35 to 45° C., and the drying time is 6 to 12 hours.
[0023] Specifically, in step 5:
[0024] The cobalt salt is cobalt nitrate hexahydrate, and the molar concentration of cobalt ions is 0.045-0.055 mol / L;
[0025] The molar concentration of sodium succinate is 0.08-0.1 mol / L;
[0026] The molar concentration of sodium sulfate is 0.009-0.011 mol / L;
[0027] The molar concentration of dimethylaminoborane is 0.09 to 0.11 mol / L.
[0028] Specifically, in step 6: the reaction time of the boronization process is 0.8 to 1.2 hours, the temperature of the vacuum drying oven is 35 to 45° C., and the drying time is 6 to 12 hours.
[0029] Specifically, in step 7, the calcination treatment is specifically as follows:
[0030] The argon gas pressure is 91-111 kPa;
[0031] The calcination temperature is 195-205°C;
[0032] Heating rate: 4.5~5.5℃ / min;
[0033] Insulation time 1.5 to 2.5 hours;
[0034] Take out after cooling naturally to room temperature.
[0035] The present invention also provides a cobalt-based oxygen evolution catalyst, which has a sheet-like matrix formed by a cobalt-based precursor material, wherein the sheet-like matrix is wrapped with cobalt-based boride nanosheets, and the cobalt-based boride nanosheets form a petal structure.
[0036] The present invention also provides the use of a cobalt-based oxygen evolution catalyst as a catalyst for oxygen evolution reaction in water electrolysis under an alkaline environment.
[0037] The catalyst of the present invention exhibits excellent electrochemical oxygen evolution reaction activity. Under the conditions of 25°C, 1M KOH electrolysis of water, it can reach 10mA / cm at a voltage of 1.479V. 2 The current density was 20 hours and the stability test performed well.
[0038] Specifically, at 10 mA / cm 2 The overpotential at the current density is less than or equal to 249mV.
[0039] The catalyst provided by the present invention has a smaller overpotential for oxygen evolution reaction, which is beneficial to the catalytic process of oxygen evolution reaction.
[0040] Preferably, in step 1, the size of the carbon cloth is 2 cm×4 cm; the amount of deionized water, ethanol, and acetone is 10 ml, and the ultrasonic time is: 15 minutes for ethanol, 15 minutes for acetone, and 15 minutes for deionized water.
[0041] Preferably, in step 2, concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1, with 15 ml of concentrated sulfuric acid and 5 ml of concentrated nitric acid.
[0042] Preferably, in step 3, the cobalt salt is cobalt nitrate hexahydrate, the molar concentration of cobalt ions is 0.06 mol / L; the molar concentration of 2-methylimidazole is 0.48 mol / L; and the reaction time is: stirring for 6 hours and settling for 6 hours.
[0043] Preferably, in step 4, the deionized water and anhydrous ethanol are rinsed alternately 2 to 3 times, the temperature of the vacuum drying oven is 40° C., and the drying time is 6 to 12 hours.
[0044] Preferably, in step 5, the cobalt salt is cobalt nitrate hexahydrate, the molar concentration of cobalt ions is 0.05 mol / L; the molar concentration of sodium succinate is 0.09 mol / L; the molar concentration of sodium sulfate is 0.01 mol / L; and the molar concentration of dimethylaminoborane is 0.1 mol / L.
[0045] Preferably, in step 6, the reaction time of the boronization process is 1 hour, the temperature of the vacuum drying oven is 40° C., and the drying time is 6 to 12 hours.
[0046] Preferably, in step 7, the calcination treatment is specifically as follows: introducing argon gas at a pressure of 1 to 101 kPa, a calcination temperature of 200° C., a heating rate of 5° C. / min, a heat preservation time of 2 hours, and taking out after naturally cooling to room temperature.
[0047] This step heat treats the catalyst material to improve the crystal structure of the material.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] 1) The cobalt-based oxygen evolution reaction catalyst prepared by the present invention is in-situ grown on carbon cloth and can be directly used as a working electrode for electrolysis reaction, and has commercial application prospects;
[0050] 2) The cobalt-based oxygen evolution reaction catalyst prepared by the present invention has a larger specific surface area, exposes more active sites, has better catalytic performance, and exhibits excellent activity and stability in alkaline electrolytes;
[0051] 3) The preparation process of the present invention is relatively mild, and the catalyst precursor can be synthesized in an aqueous solution at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a scanning electron microscope (SEM) image of the cobalt-based precursor material prepared in step 3 of Example 1 of the present invention.
[0053] Figure 2 This is a scanning electron microscope (SEM) image of the cobalt-based boride catalyst electrode material prepared in step 5 of Example 2 of the present invention.
[0054] Figure 3 This is the element distribution (EDS) diagram of the cobalt-based boride catalyst electrode material prepared in step 5 of Example 2 of the present invention.
[0055] Figure 4 The oxygen evolution reaction performance curve of the cobalt-based boride catalyst electrode material prepared in Examples 1 to 3 of the present invention in a 1M KOH environment.
[0056] Figure 5 This is a voltage-time stability test curve of the cobalt-based boride catalyst electrode material prepared in step 5 of Example 2 of the present invention in a 1M KOH environment. DETAILED DESCRIPTION
[0057] The principles and features of the present invention are described below. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0058] Example 1
[0059] A method for preparing a cobalt-based oxygen evolution reaction catalyst comprises the following steps:
[0060] Step 1, carbon cloth pretreatment: a 2cm×4cm carbon cloth was ultrasonically treated in 10ml ethanol, 10ml acetone, and 10ml deionized water for 15 minutes, and then dried in a vacuum drying oven at 40°C for 6 hours;
[0061] Step 2, hydrophilic treatment: soak the pretreated carbon cloth in a mixture of 15 ml of concentrated sulfuric acid and 5 ml of concentrated nitric acid for 12 hours, then wash with deionized water, and dry in a vacuum drying oven at 40°C for 6 hours;
[0062] Step 3, preparation of cobalt-based precursor material: add 1.74g Co(NO3)2·6H2O to 100ml of deionized water to form solution A, and put the treated carbon cloth into solution A for ultrasonic treatment for 5 minutes; add 3.96g 2-methylimidazole to 100ml of deionized water and dissolve it in deionized water to form solution B, and slowly pour it into solution A and stir for 6 hours, and then let it stand for 6 hours; take out the carbon cloth, rinse it with deionized water and anhydrous ethanol alternately for 3 times, and then put it into a 40°C vacuum drying oven for 6 hours to prepare a cobalt-based precursor material;
[0063] Step 4: Add 1.5 g Co(NO3)2·6H2O, 1.45 g C4H4Na2O4, 0.72 g Na2SO4 and 0.6 g C2H 10 BN, stir for 5 minutes to dissolve it, and a mildly boronized reaction solution can be obtained; the prepared cobalt-based precursor material is placed in the solution to react for 1 hour, then taken out, washed with deionized water, and dried in a vacuum drying oven at 40°C for 6 hours.
[0064] Example 2
[0065] A method for preparing a cobalt-based oxygen evolution reaction catalyst comprises the following steps:
[0066] Step 1, carbon cloth pretreatment: a 2cm×4cm carbon cloth was ultrasonically treated in 10ml ethanol, 10ml acetone, and 10ml deionized water for 15 minutes, and then dried in a vacuum drying oven at 40°C for 6 hours;
[0067] Step 2, hydrophilic treatment: soak the pretreated carbon cloth in a mixture of 15 ml of concentrated sulfuric acid and 5 ml of concentrated nitric acid for 12 hours, then wash with deionized water, and dry in a vacuum drying oven at 40°C for 6 hours;
[0068] Step 3, preparation of cobalt-based precursor material: add 1.74g Co(NO3)2·6H2O to 100ml of deionized water to form solution A, and put the treated carbon cloth into solution A for ultrasonic treatment for 5 minutes; add 3.96g 2-methylimidazole to 100ml of deionized water and dissolve it in deionized water to form solution B, and slowly pour it into solution A and stir for 6 hours, and then let it stand for 6 hours; take out the carbon cloth, rinse it with deionized water and anhydrous ethanol alternately for 3 times, and then put it into a 40°C vacuum drying oven for 6 hours to prepare a cobalt-based precursor material;
[0069] Step 4: Add 1.5 g Co(NO3)2·6H2O, 1.45 g C4H4Na2O4, 0.72 g Na2SO4 and 0.6 g C2H 10BN, stirring for 5 minutes to dissolve it, to obtain a mildly borated reaction solution; the prepared cobalt-based precursor material was placed in the solution for reaction for 1 hour, then taken out, washed with deionized water, and dried in a vacuum drying oven at 40°C for 6 hours;
[0070] Step 5: calcining the material obtained in the previous step in an argon atmosphere of 101 kPa at a temperature of 200°C, a heating rate of 5°C / min, and a holding time of 2 hours. After naturally cooling to room temperature, the material is taken out to obtain a cobalt-based boride catalyst electrode material.
[0071] Example 3
[0072] This embodiment is basically the same as embodiment 2, except that step 5: the calcination temperature is different. The calcination treatment is carried out in an argon atmosphere of 101 kPa, the calcination temperature is 500°C, the heating rate is 5°C / min, the insulation time is 2 hours, and the material is taken out after naturally cooling to room temperature to obtain a cobalt-based boride catalyst electrode material.
[0073] Use scanning electron microscopy to observe the morphology of the catalyst material:
[0074] Figure 1 This is a SEM image of the cobalt-based precursor material prepared in step 3 of Example 1. It can be clearly seen that the cobalt-based precursor material is a sheet array structure that grows evenly on the surface of the carbon cloth fiber.
[0075] Figure 2 This is a SEM image of the cobalt-based precursor material prepared in step 5 of Example 2. It can be clearly seen that the nanosheets of the cobalt-based boride form a petal structure and are evenly coated on the sheet-like matrix formed by the cobalt-based precursor material.
[0076] Figure 3 This is an element distribution diagram of the cobalt-based boride catalyst electrode material prepared in step 5 of Example 2. From the diagram, it can be seen that the elements Co, O, N, and B are evenly distributed on the cobalt-based boride material.
[0077] The cobalt-based boride catalyst materials prepared in Examples 1 to 3 were applied to the electrolysis of water for oxygen evolution reaction, and the electrochemical performance of the catalysts was tested using a Chenhua CHI 760E electrochemical workstation. The test system was a three-electrode system: a carbon rod was used as a counter electrode, Hg / HgO was used as a reference electrode, a platinum electrode clamp was used to hold the prepared cobalt-based boride catalyst electrode material as a working electrode, and 1.0M KOH was used as an electrolyte solution, forming a three-electrode test system. The test results are shown in Figure 2. Figure 4 , Figure 5 shown.
[0078] Figure 4The oxygen evolution reaction performance curve of the cobalt-based boride catalyst electrode material prepared in Examples 1 to 3 in a 1.0M KOH alkaline environment. The test results show that the sample prepared in Example 2 has the best oxygen evolution reaction catalytic performance at 10 mA / cm 2 The overpotential at the current density is only 249 mV, which is lower than that of other embodiments.
[0079] Figure 5 The voltage-time stability curve of the cobalt-based boride catalyst electrode material prepared in Example 2 in a 1.0 M KOH alkaline environment at 10 mA / cm 2 It can operate stably for up to 20 hours at the current density.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a cobalt-based oxygen evolution catalyst, characterized in that: The following steps are involved: Step 1: Pretreatment: The carbon cloth electrode is ultrasonically treated in ethanol, acetone, and deionized water in turn, and then cleaned and dried to obtain the carbon cloth electrode material; Step 2: Hydrophilic treatment: Soak the carbon cloth in a mixture of concentrated sulfuric acid and concentrated nitric acid, then wash and dry with deionized water; Step 3: dissolving a certain amount of cobalt salt in deionized water to form solution A; dissolving a certain amount of 2-methylimidazole in deionized water to form solution B; Step 4: placing the carbon cloth obtained in step 2 into solution A for 5 minutes of ultrasonic treatment, then slowly adding solution B and stirring continuously for reaction; washing the carbon cloth after the reaction with deionized water and anhydrous ethanol alternately, and then placing it in a vacuum drying oven for drying to prepare a carbon cloth having a cobalt-based precursor material; Step 5: Weigh a certain amount of cobalt salt, sodium succinate, sodium sulfate and dimethylamino borane, and add deionized water to prepare a uniform solution C; Step 6: Place the carbon cloth with the cobalt-based precursor material obtained in step 4 into the solution C prepared in step 5 to perform a mild boronization process, take it out after the reaction, wash it with deionized water, and then place it in a vacuum drying oven for drying; Step 7: calcining the material obtained in step 6 to obtain a cobalt-based boride catalyst electrode material.
2. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 2: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:(0.9-1.1); The soaking time is 10 to 14 hours.
3. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 3: The cobalt salt is cobalt nitrate hexahydrate, and the molar concentration of cobalt ions is 0.055-0.065 mol / L; The molar concentration of 2-methylimidazole is 0.45-0.50 mol / L; The reaction time is: stirring for 5.5 to 6.5 hours and settling for 5.5 to 6.5 hours.
4. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 4: the temperature of the vacuum drying oven is 35 to 45° C., and the drying time is 6 to 12 hours.
5. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 5: The cobalt salt is cobalt nitrate hexahydrate, and the molar concentration of cobalt ions is 0.045-0.055 mol / L; The molar concentration of sodium succinate is 0.08-0.1 mol / L; The molar concentration of sodium sulfate is 0.009-0.011 mol / L; The molar concentration of dimethylaminoborane is 0.09 to 0.11 mol / L.
6. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 6: the reaction time of the boronization process is 0.8 to 1.2 hours, the temperature of the vacuum drying oven is 35 to 45° C., and the drying time is 6 to 12 hours.
7. The method for preparing a cobalt-based oxygen evolution catalyst according to claim 1, characterized in that: In step 7, the calcination treatment is specifically: The argon gas pressure is 91-111 kPa; The calcination temperature is 195-205°C; Heating rate: 4.5~5.5℃ / min; Insulation time 1.5 to 2.5 hours; Take out after cooling naturally to room temperature.
8. A cobalt-based oxygen evolution catalyst prepared by the method according to any one of claims 1 to 7, characterized in that: A cobalt-based precursor material is loaded on the carbon cloth to form a sheet-like matrix, and the sheet-like matrix is wrapped with a nano-flower-like structure, and the flower-like structure is formed by sheet-like cobalt-based boride as petals.
9. An application of the cobalt-based oxygen evolution catalyst according to claim 8, characterized in that: As a catalyst for oxygen evolution reaction in water electrolysis under alkaline environment.
10. The use according to claim 9, characterized in that: At 10mA / cm 2 The overpotential at the current density is less than or equal to 249mV.
Citation Information
Patent Citations
A Co-B / Co-MOF nanomaterial, its preparation method and application
CN113463125B
Method for preparing CoB amorphous alloy based on ZIF-67 framework material
CN105385965A
Preparation Method and Use of Cobalt Nanoparticle / Boron Nitride Composite
US20230264179A1